MEMORY SPACE IN ELENA ISAEVA’S VERBATIM-PIECE "ABOUT MY MOTHER AND ABOUT ME" - Alexandra Valerievna Ekabsons (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the artistic space as one of the aspects of the memories of the heroes of the play. The play’s documentary nature (school compositions in two acts) is based on the author’s writings written during classes in a literary circle. The author of the play regulates the flow of time in the following way: time flows most dynamically in the author’s comments; they are numerous, lively and addressed directly to the recipient; time slows down a little in the memories. Memories are devoid of chronological framework, on the one hand, but are subordinate to the storyline of the document (composition), on the other hand.